2022
DOI: 10.1007/s10266-022-00734-4
|View full text |Cite
|
Sign up to set email alerts
|

Immediate dental implant placement in post-extraction-infected sites decontaminated with Er,Cr:YSGG laser: a retrospective cohort study

Abstract: Dental implants placed in fresh extraction alveoli provide several advantages, including shorter treatment periods and improved patient comfort. After a compromised tooth extraction, the Er,Cr:YSGG laser can considerably reduce bacterial concentration. The objective of this controlled study conducted after at least 1 year of follow-up was to compare the use of immediate post-extraction implants in infected sites treated with laser (test group) versus conventional implants in edentulous sites (control group) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…After 10 years, the tooth was still vital, but severe external resorption was observed [ 21 ]. In addition, a study also reported that laser application to the socket after extraction not only reduces the bacterial load but also increases epithelialization in the gingival pocket and increases healing [ 22 ]. The fact that no laser was applied to the post-extraction socket might be a limitation of the first case.…”
Section: Discussionmentioning
confidence: 99%
“…After 10 years, the tooth was still vital, but severe external resorption was observed [ 21 ]. In addition, a study also reported that laser application to the socket after extraction not only reduces the bacterial load but also increases epithelialization in the gingival pocket and increases healing [ 22 ]. The fact that no laser was applied to the post-extraction socket might be a limitation of the first case.…”
Section: Discussionmentioning
confidence: 99%
“…Aleksandra Križaj Dumic et al performed degranulation with an Er:YAG laser at 160 mJ and 15 Hz [ 18 ]. Crippa R et al recommended a power of 2 W and 15 Hz for debridement and decontamination [ 19 ]. In this study, the parameters were an energy of 100 mJ, a frequency of 20 Hz and an output power of 2 W. Further experiments should be performed to determine the appropriate laser parameters for ARP.…”
Section: Discussionmentioning
confidence: 99%
“…Er:YAG lasers are minimally invasive, accurate and highly efficient, and they are widely used in dentistry, including in the treatment of deep caries and peri-implantitis and in surgical resection. Recently, an Er:YAG laser was used in degranulation when performing ARP [ 18 , 19 ]. However, the Er:YAG laser was applied in combination with other types of lasers [ 17 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the rehabilitation of the mandibular incisors and/or maxillary lateral incisors (MI/MxLI) is a challenge for clinicians. Immediate dental implants could be a good treatment choice, but this kind of surgery is not always possible [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%